Haemozoin as a marker of placental parasitization. - Mcgready, R; Brockman, A; Cho, T; Levesque, M; Tkachuk, A; Meshnick, SR; Nosten, F (2002)
Both Plasmodium vivax and P. falciparum malaria can cause the delivery of low birthweight babies. In this report, we have quantitated haemozoin levels in placentas from women living on the Thai-Burmese border in a region of low transmission for both P. falciparum and P. vivax malaria from June 1995 to January 2000. P. falciparum malaria infections during pregnancy lead to the accumulation of haemozoin (malaria pigment) in the placenta, especially in infections near term and in primigravid pregnancies. Haemozoin concentration was not associated with adverse birth outcomes. Women with P. vivax infections during pregnancy do not have measurable levels of placental haemozoin suggesting that P. vivax-infected erythrocytes do not accumulate in the placenta as much as P. falciparum-infected ones.